2022
DOI: 10.1037/men0000381
|View full text |Cite
|
Sign up to set email alerts
|

“We are okay to be ourselves”: Understanding gay men’s friendships with heterosexual and gay men.

Abstract: Friendships are crucial for well-being (Narr et al., 2019), and this may particularly be the case for gay men (Nardi, 1999; Nardi & Sherrod, 1994). One-way friendships have been understood is through the lens of gender segregation, which posits that same-gender friendships are more appropriate and safer than cross-gender friendships, due to a presumed lack of sexual or romantic interest between same-gender friends and similarities in communication preferences. This assertion may not hold true for gay men; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…Supporting recent quantitative research which found young sexual minorities to have same-gender, cross-sexuality friendships (Davis & Mehta, 2022; Gillespie et al, 2015), mostly gay participants in this study reported friendship diversity, including friendships with straight men with whom they were open about their sexuality. For example, James, a 22-year-old mostly gay student from California, said, “My best friend, David, is 100% straight…Frat guys have much more of an open and liberating perspective on male sexuality… They’re very tolerant [of gay guys].” Similarly, Matthew, a 19-year-old mostly gay student who plays for his university’s football team, said, “I have a few close [straight] friends, mainly Mason and Joey, and there is no homophobia from them.…”
Section: Diversity In Friendship Group Compositionsupporting
confidence: 80%
See 3 more Smart Citations
“…Supporting recent quantitative research which found young sexual minorities to have same-gender, cross-sexuality friendships (Davis & Mehta, 2022; Gillespie et al, 2015), mostly gay participants in this study reported friendship diversity, including friendships with straight men with whom they were open about their sexuality. For example, James, a 22-year-old mostly gay student from California, said, “My best friend, David, is 100% straight…Frat guys have much more of an open and liberating perspective on male sexuality… They’re very tolerant [of gay guys].” Similarly, Matthew, a 19-year-old mostly gay student who plays for his university’s football team, said, “I have a few close [straight] friends, mainly Mason and Joey, and there is no homophobia from them.…”
Section: Diversity In Friendship Group Compositionsupporting
confidence: 80%
“…Heterosexual men’s friendships have traditionally been framed as lacking emotional depth and segregated by gender, class, race and sexuality (e.g., Bank & Hansford, 2000; Berger & Mallon, 1993). While quantitative research is increasingly finding cross-sexuality friendships and diversity in group composition (e.g., Davis & Mehta, 2022; Gillespie et al, 2015), scant qualitative work on this phenomenon exists. Drawing on interviews with 25 young men with non-exclusive sexual orientations from an elite university, this study advances our understanding of the contemporary dynamics of men’s friendships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in contrast to the earlier findings, sexual minority young women had the most same-gender friends. In addition, qualitative studies of the friendships of gay and lesbian emerging adults have found similar results (Davis & Mehta, 2021; Mehta, 2016). Taken together, these studies provide some support for the idea that gender socialization in childhood peer networks varies by sexual orientation and that all but heterosexual men are socialized in peer contexts with girls.…”
Section: Introductionmentioning
confidence: 82%